Empowering Education Through Pantun: A Stylistic Approach to Motivation and Meaning - Putri Sion Br Siallagan; Rosmawaty Harahap (Journal of Aceh Studies, 2025)
Background of the problem: Pantun, a traditional Malay poetic form, has historically functioned as a vehicle for cultural expression and moral education. Pantun possesses potential as a motivational and educational instrument within contemporary education. Purpose: This study seeks to examine the stylistic components of educational pantun and their function in cultivating a passion for studying and imagining a more promising future. Method: The study uses a descriptive method and library research to analyze selected educational pantun by looking at elements like word choice, rhyme, figurative language, imagery, and meaning. Data were obtained from digital libraries, scholarly publications, and pertinent literature. Result: The results indicate that pantun utilizes elaborate linguistic elements, including metaphor, rhythm, and vivid imagery, to communicate themes of discipline, perseverance, and the transformational influence of education. These stylistic tactics not only augment the aesthetic allure of the pantun but also strengthen its motivational efficacy. Implication: The study highlights the significance of traditional literary forms in modern educational discussions and proposes that incorporating pantun into learning settings can enhance cultural appreciation and student involvement. This study enhances the fields of stylistics and educational linguistics by illustrating the revitalization of classical poetic forms to advance contemporary teaching objectives.